Notes on Gymnopetalum (Cucurbitaceae) from the Lesser Sunda Islands, Indonesia - MENTARI PUTRI PRATAMI; YESSI SANTIKA; RUGAYAH RUGAYAH (Nusantara Bioscience, 2026)
Abstract. Pratami MP, Santika Y, Rugayah. 2026. Notes on Gymnopetalum (Cucurbitaceae) from the Lesser Sunda Islands, Indonesia. Nusantara Bioscience 18 (1): n180101. https://doi.org/10.13057/nusbiosci/n180101. Four species of Gymnopetalum (G. chinensis, G. orientale, G. scabrum, and G. pectinatum) have been reported for the Malesian Region, all of which can be found in the Lesser Sunda Islands, Indonesia. The genus is closely related to Trichosanthes, and one species, G. orientale, morphologically resembles T. quinquangulata. Moreover, molecular data place Gymnopetalum as a section of Trichosanthes (=Trichosanthes sect. Tripodanthera). In this study, morphology and leaf anatomy observation have been conducted on BO collections of Gymnopetalum from the Lesser Sunda Islands. Anatomical observation of leaf paradermal sections follows the method of Sass and Cutler. An unidentified specimen collected from Lombok (Kahono, Nakano, and Abbas 2005-36) resembles G. orientale in floral characters but differs in leaf shape. Anatomical data support morphological data that the specimen is similar to G. orientale in epidermis characters. They have the same epidermis cell shape i.e. irregularly shaped with shallowly sinuous anticlinal walls, but differ in size only, G. orientale has epidermal cell sizes of 19-24.80 × 12.40-14.88 µm (upper) and 19.84-21.32 × 12.40-14.88 µm (lower), whereas the Kahono Nakano, Abbas 2005-36 specimen has epidermal cell sizes of 27.28-29.76 × 14.88-17.36 µm (upper) and 24.80-27.28 × 17.36-19.84 µm (lower). These differences fall within morphological variation and support the identification of the Lombok material as G. orientale. The anatomical evidence corroborates previous morphological and molecular studies, indicating intermediate characters between G. orientale and T. quinquangulata, reinforcing the close evolutionary relationship between the two genera. This study contributes additional morphological and anatomical data supporting the phylogenetic placement of Gymnopetalum within Trichosanthes.